Shoe dog [compact disc, unabridged] : a memoir by the creator of Nike - Knight, Philip H., 1938- (Audioworks, an imprint of Simon & Schuster Audio, 2016)
In this candid and riveting memoir, for the first time ever, Nike founder and CEO Phil Knight shares the inside story of the company's early days as an intrepid start-up and its evolution into one of the world's most iconic, game-changing, and profitable brands.